2002
DOI: 10.1136/jnnp.72.5.615
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric illness and subsequent traumatic brain injury: a case control study

Abstract: Objective: To determine whether psychiatric illness is a risk factor for subsequent traumatic brain injury (TBI). Methods: Case control study in a large staff model health maintenance organisation in western Washington State. Patients with TBI, determined by International classification of diseases, 9th revision, clinical modification (ICD-9-CM) diagnoses, were 1440 health plan members who had TBI diagnosed in 1993 and who had been enrolled in the previous year, during which no TBI was ascertained. Three healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 50 publications
1
49
0
Order By: Relevance
“…Hibbard et al [13] found that 51% of TBI patients had pre-injury psychiatric disorders, most commonly major depression or substance use disorders that occurred at double the rates reported in community samples. A case control study by Fann et al [14] found that 18.2% of cases with TBI had a psychiatric ICD-9-CM diagnosis in the year prior to TBI compared to 9.7% of controls. In a study looking at schizophrenia pedigrees, Malaspina et al [15] found a higher prevalence of TBI among those with schizophrenia; however, it was difficult to distinguish whether early features of schizophrenia predispose one to TBI or if head injury further increases the risk of expression of schizophrenia in a genetically susceptible individual.…”
Section: Tbi and Suicidementioning
confidence: 97%
“…Hibbard et al [13] found that 51% of TBI patients had pre-injury psychiatric disorders, most commonly major depression or substance use disorders that occurred at double the rates reported in community samples. A case control study by Fann et al [14] found that 18.2% of cases with TBI had a psychiatric ICD-9-CM diagnosis in the year prior to TBI compared to 9.7% of controls. In a study looking at schizophrenia pedigrees, Malaspina et al [15] found a higher prevalence of TBI among those with schizophrenia; however, it was difficult to distinguish whether early features of schizophrenia predispose one to TBI or if head injury further increases the risk of expression of schizophrenia in a genetically susceptible individual.…”
Section: Tbi and Suicidementioning
confidence: 97%
“…Follow-up studies of patients hospitalized after TBI have found that psychiatric conditions are associated with poorer outcomes, even in patients with mild head injuries [10]. Premorbid psychiatric conditions have been identified as increasing the risk of TBI in hospital-based samples and casecontrol studies [8,9]. Hospital-based studies have shown increased suicide rates following TBI that have been attributed to psychosocial disadvantage and psychiatric disorders resulting from TBI [11,12].…”
Section: Introductionmentioning
confidence: 97%
“…Clinical studies have shown that mood disturbances are among the most common emotional problems in patients with TBI, with depressive disorders reported to occur in 20-50% of cases [7]. An increased risk for depression persists many decades following TBI [8,9]. Follow-up studies of patients hospitalized after TBI have found that psychiatric conditions are associated with poorer outcomes, even in patients with mild head injuries [10].…”
Section: Introductionmentioning
confidence: 97%
“…However, whether these traits-in addition to those identified as being transdiagnostic-reflect post-injury changes in personality and psychopathology or whether they predate the injury or have become exacerbated as a result of the TBI is difficult to establish given the temporal constraints of addressing this question. Indeed, previous longitudinal studies have reported evidence of pre-existing elevations in somatoform symptomatology amongst persons who later sustained head injuries [47,48].…”
Section: Discussionmentioning
confidence: 98%